2019
DOI: 10.1111/irv.12702
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of H7N9 virus antibody response 2 years after infection

Abstract: We measured antibodies against H7N9 virus 2 years after infection in 14 patients who were infected during October 2016‐September 2017. Approximately 2 years after infection, antibody titers ≥10 were detectable in 13 (92.9%) patients. Three (21.4%) of 14 patients had hemagglutination inhibition titers ≥40, and their geometric mean titer (GMT) was 20 (95% CI 15.7‐28.1), whereas 10 (71.4%) and all 14 (100%) of the 14 patients had titers ≥40, and GMTs at 34.4 (95% CI 25.7‐51.2) and 73.45 (54.7‐106.7) for neuramini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Serology studies have shown that human H7N9 virus infection stimulates the induction of H7-reactive antibody responses that persist for at least several years ( 10 , 11 , 24 , 38 ). Kinetic monitoring of such responses revealed that heterosubtypic H7 and H3 binding/neutralizing antibody responses typically appear and peak earlier than H7 subtype responses, likely mediated by memory recall of H3-reactive clones ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serology studies have shown that human H7N9 virus infection stimulates the induction of H7-reactive antibody responses that persist for at least several years ( 10 , 11 , 24 , 38 ). Kinetic monitoring of such responses revealed that heterosubtypic H7 and H3 binding/neutralizing antibody responses typically appear and peak earlier than H7 subtype responses, likely mediated by memory recall of H3-reactive clones ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…The single H7N9 subtype had caused at least 616 deaths in humans since it emerged in 2013 (7,8). Previous serology studies detected relatively robust antibody responses against the H7 HA after H7N9 infection that decreased but remained detectable after several years (9)(10)(11)(12). Phylogenetic analyses of H7Nx viruses based on the H7 HA gene deduced two major genetic lineages, designated North American and Eurasian (13).…”
Section: Introductionmentioning
confidence: 96%